Improving Recovery from Oil Sandstone Reservoir by Re-inject of Produced Water by Using Eclipse_E300 Software - Madi Abduallah Naser (Journal of Pure & Applied Sciences, 2018)
Re-injected produced water into sandstone reservoir at the initial stage is to maintain reservoir pressure, replace produced oil, and provide for the recovery of oil by water displacement. Water injection essentially increases the rate of oil field development and in many cases permits increased oil recovery. This paper demonstrates a successful simulation case study based on a field data of project. The objective of this study is to improve recovery from oil sandstone reservoir by four re-inject wells of produced water within ten years for twenty-six oil production wells. In order to do that, first, the simulation 3-D model built by using advanced reservoir simulation software (Schlumberger Eclipse_E100) [1]. Second, select the best zone for water displacement. Third, select the best location for injector well. Fourth, determine the injector well depth. Fifth, make a sensitive of water injection rate to determine the optimum rate. Sixth, re-inject water produced with optimum rate.Results obtained in this research show that, the location of injection wells will influence the oil production rate and recoverable reserve. Time management also one of the most important factors which may influence the oil recovery. The right time to inject water is very important. Results of this study suggest that simultaneous re-inject of produced water will increase the recovery factors by up to 15 % of originally oil in place. This present study may hopeful be useful as reference of information for any operating company to establish the re-injection of produced water of field.